Investigation of mechanical behavior of reinforced u-profile composites under low velocity impact - Uslu, Merve; Kaman, Mete Onur; Albayrak, Mustafa; Yanen, Cenk; Dag, Serkan; Erdem, Serkan; Turan, Kadir (My University, 2024)
In this study, the impact resistance of reinforced composite panels with unsupported, and U profile supported by I profile was numerically examined. For this purpose, firstly, unsupported glass fiber/epoxy composite panels were designed, and then I-profile composite supports were added to these panels. The impact strength, and damage behavior of supported, and unsupported specimens under low-velocity impact were compared numerically. In the analysis, the MAT22 material card, also known as the Chang-Chang damage model for composite material, was used in the LS-DYNA program. As a result of the analysis, maximum damage load of the unsupported specimen is determined to be approximately 294 N. It was determined that by adding an I profile to the structure, the maximum damage load increased to 543 N. It was seen that the added I profile supports increased the maximum contact force of the composite structure by approximately 85%. Fiber breakage damages were observed in both supported, and unsupported specimens. However, with the use of I profile support, the damaged area was further reduced. It has been determined that under low-velocity impact, supported specimens exhibit more rigid material behavior than unsupported specimens.
Keywords: Impact; u-profile composite; Chang-Chang failure criteria; I profile; MAT22.